2022
DOI: 10.1021/acsami.2c11968
|View full text |Cite
|
Sign up to set email alerts
|

Robust Antibacterial Activity of Xanthan-Gum-Stabilized and Patterned CeO2–x–TiO2 Antifog Films

Abstract: Increased occurrence of antimicrobial resistance leads to a huge burden on patients, the healthcare system, and society worldwide. Developing antimicrobial materials through doping rare-earth elements is a new strategy to overcome this challenge. To this end, we design antibacterial films containing CeO2–x –TiO2, xanthan gum, poly­(acrylic acid), and hyaluronic acid. CeO2–x –TiO2 inks are additionally integrated into a hexagonal grid for prominent transparency. Such design yields not only an antibacterial effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…However, a coating containing TiO 2 combined with a second metal oxide (such as WO 3 , ZnO, SiO 2 , or ZrO 2 ) has been proved to induce the absorption spectrum of TiO 2 to extend from ultraviolet to visible light, enhancing the hydrophilicity of TiO 2 under natural light. [136][137][138][139] In addition, researchers found that Fe 3+ is the best effective ion to induce the absorption spectrum of TiO 2 to extend from ultraviolet to visible light. 34,[140][141][142] With this in mind, Yang and his colleagues 57 prepared a series of Fe 3+ -doped TiO 2 films using the sol-gel method.…”
Section: Coating Materialsmentioning
confidence: 99%
“…However, a coating containing TiO 2 combined with a second metal oxide (such as WO 3 , ZnO, SiO 2 , or ZrO 2 ) has been proved to induce the absorption spectrum of TiO 2 to extend from ultraviolet to visible light, enhancing the hydrophilicity of TiO 2 under natural light. [136][137][138][139] In addition, researchers found that Fe 3+ is the best effective ion to induce the absorption spectrum of TiO 2 to extend from ultraviolet to visible light. 34,[140][141][142] With this in mind, Yang and his colleagues 57 prepared a series of Fe 3+ -doped TiO 2 films using the sol-gel method.…”
Section: Coating Materialsmentioning
confidence: 99%
“…TEM analysis was executed through the utilization of a JEOL TEM equipped with an in-column Omega-type energy filter (JEM-2200FS, Joel, Japan) (Wu et al, 2021(Wu et al, , 2022a(Wu et al, , 2022bPan et al, 2016Pan et al, , 2017Pan et al, , 2022aGuo et al, 2022). 5 μL of the sample after a 100-fold dilution was added to a TEM grid (Kung et al, 2018(Kung et al, , 2020Tseng et al, 2020) (Carbon Film Supported Copper Grid, 200 Meshes, Electron Microscopy Sciences, USA) till the solvent was completely evaporated (Yang et al, 2022;Pan et al, 2022b;Yu et al, 2021;Kung et al, 2021).…”
Section: Tem Analysismentioning
confidence: 99%
“…One bacterial colony of every bacterial strain from an agar plate was taken and incubated in 10 mL LB in a 50 mL Falcon tube at 160 rpm and 37 • C overnight. 100 μL overnight culture was added into 10 mL fresh LB and subsequently cultivated for approximately 2 h to reach exponential growth (Guo et al, 2022;Hegemann et al, 2022;Milionis et al, 2020).…”
Section: Bacterial Preparationmentioning
confidence: 99%
“…Taxonomy is applied in different systems, e.g., mammalian systems, insect expression systems, bacterial systems, lament fungi, yeasts, and unicellular cells. 15,[46][47][48][49][50][51][52][53][54][55][56][57] Escherichia coli is therefore extensively used thanks to the fast growth kinetics and low production costs, 58,59 consequently leading to substantial application in protein taxonomy through various plasmid expressions. 59,60 Nowadays, biologists are increasingly applying evolutionary developmental biology to address environmental challenges, food crises, and health care, in which tree-shaped diagrams, namely phylogenetic trees, are oen utilized to understand the evolutionary relationships between the species and populations, and to solve the respective challenges.…”
Section: Introductionmentioning
confidence: 99%